2003
DOI: 10.3354/meps249223
|View full text |Cite
|
Sign up to set email alerts
|

Onshore-offshore variations in copepod community structure off the Oregon coast during the summer upwelling season

Abstract: During the summer of 1994, 1996, and 1997, we conducted hydrographic and plankton surveys of the upper 70 m in the nearshore, the continental shelf, and off-shelf oceanic waters off Oregon, USA. Copepod densities and biomass were estimated along 4 transects from each cruise. The on-shelf copepod biomass was 2.8 times greater than off-shelf biomass. Nonmetric multidimensional scaling identified an on-shelf and an off-shelf copepod community. The change in community composition usually occurred at or slightly of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 38 publications
4
42
0
Order By: Relevance
“…Fisheries Investigations (CalCOFI) protocol (Smith et al 1985) with a 0.25 m diameter, 150 µm mesh CalVET net. See Morgan et al (2003) for complete methods. For euphausiids and chaetognaths, the entire sample was usually examined, or (for 4 samples) a 1 ⁄ 4 or 1 ⁄ 2 split was examined because numbers of euphausiid furcilia of all genera exceeded 200.…”
Section: Introductionmentioning
confidence: 99%
“…Fisheries Investigations (CalCOFI) protocol (Smith et al 1985) with a 0.25 m diameter, 150 µm mesh CalVET net. See Morgan et al (2003) for complete methods. For euphausiids and chaetognaths, the entire sample was usually examined, or (for 4 samples) a 1 ⁄ 4 or 1 ⁄ 2 split was examined because numbers of euphausiid furcilia of all genera exceeded 200.…”
Section: Introductionmentioning
confidence: 99%
“…gibbula, which was significantly abundant in the samples collected one month after the upwelling are the most abundant in summer or autumn on the onshore side of the Kuroshio (Furuhashi 1961, Itoh & Mizushima 1999, Itoh et al 2005. Morgan et al (2003) found that warm water species were distributed in the offshore waters of Oregon during upwelling periods. The changes of the copepod community structure during the periods of upwelling in Tosa Bay may be due to an increase in species that prefer low water temperatures and a decrease of species that prefer warm water temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…In the California Current, the abundances of Calanus marshallae Frost, 1974, Pseudocalanus mimus Frost, 1989 and Acartia longiremis (Lilljeborg, 1853) at the on-shelf stations were higher than those at the off-shelf stations during the upwelling season (Morgan et al 2003). In the upwelling zones during the upwelling periods, Centropages brachiatus (Dana, 1849) and Eucalanus inermis Giesbrecht, 1892 were abundant off Peru (Gutiérrez et al 2005), Calanus chilensis Brodsky, 1959, Paracalanus cf.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During DYNAPROC 2 cruise, all individuals from the genus Mesocalanus belong to the species tenuicornis. M. tenuicornis is an oceanic species which was collected in all temperate and subtropical waters (Beaugrand et al, 2002;Keister et al, 2003;Morgan et al, 2003;Mackas et al, 2005). In the Ligurian Sea, Pinca and Dallot (1995) suggested that the central zone is favourable environment for the development of the large copepods species like M. tenuicornis.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%